Suffering is not enough: Assisted dying for people with mental illness - Trachsel, Manuel (Bioethics, 2022)
Persons with mental disorders who are resistant to evidence-based treatment can be referred to as patients with severe and persistent mental illness (SPMI). Some patients with SPMI develop a strong wish for assisted dying. Switzerland has the longest history of non-medicalized assisted dying, which is considered a civil right even in non-pathological situations. Public debate in Switzerland about the issue of suffering in the context of assisted dying is current and ongoing. The Swiss Academy of Medical Sciences recently revised its end-of-life policy and specified intolerable suffering due to severe illness or functional limitations (and acknowledged as such by a physician) as a core criterion for assisted dying. We argue that suffering is a necessary but insufficient condition for assisted dying, and that the criteria should also include decision-making capacity and refractoriness of suffering. We further contend that suffering is a subjective experience that can only be quantified by the patient and cannot be objectively compared across individuals. Some patients with SPMI and refractory suffering who maintain decision-making capacity will meet the criteria for assisted dying. We advocate for palliative psychiatric care that relinquishes any disease-modifying therapy, accepts limited survival chances, and focuses on measures that enhance the patient's quality of life, understood in a very broad sense beyond only health-related quality of life. This approach should also relieve suffering as much as possible while remaining open to the possibility of assisted dying following conscientious assessment of the criteria.